2009
DOI: 10.1124/dmd.108.024638
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sandwich-Cultured Hepatocytes As an in Vitro Model to Assess the Hepatobiliary Disposition of Copper

Abstract: ABSTRACT:Sandwich-cultured hepatocytes (SCH) from rats (SCRH), dogs (SCDH), and humans (SCHH) were used as an in vitro model to assess the hepatobiliary disposition of copper (Cu). The expression of Cu transporters, ceruloplasmin synthesis, Cu uptake, and biliary excretion and species differences in drug-induced alterations in Cu disposition were determined in SCH from all species. Western blot analysis verified basolateral Cu uptake transporter 1 (CTR1) and canalicular Cu efflux transporter (ATP7B) expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…From then, levels remained high until about the second week of life, thereafter decreasing to adult levels by six weeks of age (Terao and Owen 1977 ). In mammalian cells, copper import is primarily mediated by CTR1 protein (Ansede et al 2009 ; Kim et al 2009 ; Lee et al 2002 ; Nose et al 2006 ; Van den Berghe and Klomp 2010 ). Kuo et al ( 2006 ) showed that in mice and rats CTR1 expression is regulated by copper status (Bauerly et al 2005 ; Kuo et al 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…From then, levels remained high until about the second week of life, thereafter decreasing to adult levels by six weeks of age (Terao and Owen 1977 ). In mammalian cells, copper import is primarily mediated by CTR1 protein (Ansede et al 2009 ; Kim et al 2009 ; Lee et al 2002 ; Nose et al 2006 ; Van den Berghe and Klomp 2010 ). Kuo et al ( 2006 ) showed that in mice and rats CTR1 expression is regulated by copper status (Bauerly et al 2005 ; Kuo et al 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, cyclosporine A and glyburide decreased total accumulation (cells+bile), increased cellular accumulation, and decreased BEI and Cl biliary of deuterium-labeled taurocholate (d 8 -TC), suggesting that bile acid efflux was affected primarily (Ansede et al, 2009 in press). In contrast, erythromycin-estolate, troglitazone and bosentan decreased d 8 -TC accumulation (both cells+bile and cells), BEI and Cl biliary of d 8 -TC, suggesting that bile acid uptake was the predominant pathway affected.…”
Section: Sandwich-cultured Hepatoctyes As a Tool To Predict Drug Intementioning
confidence: 99%
“…SCH recently were evaluated for the potential to assess hepatobiliary disposition of copper (Ansede et al, 2009). Copper (Cu) is an essential nutrient necessary for the activity of various enzymes, but also can accumulate to toxic levels when Cu elimination is disrupted by drugs or genetic disorders, such as in Wilson's Disease, which is characterized by massive Cu accumulation in lysosomes and lack of excretion in bile, the major route (85%) of Cu elimination.…”
Section: Use Of Sandwich-cultured Hepatocytes To Predict Drug-inducedmentioning
confidence: 99%